تقصي البيلة الجرثومية اللاعرضية عند الحوامل - الدالي, عصام; مرعي, رئيفة; خضر, حسان (Latakia University Journal -Medical Sciences Series, 2019)
لقد درسنا الحوامل مراجعات العيادة النسائية وقسم التوليد وأمراض النساء في مشفى الأسد الجامعي باللاذقية. بشكايات مختلفة بعيدة عن المشاكل البولية. بين 1/7/2003 و1/6/2004 قد وجدنا 35 حالة بيلة جرثومية من أصل 449 حامل مراجعة بنسبة 7.8% . كانت البيلة الجرثومية اللاعرضية مرتفعة مع تقدم عمر الحامل وتعدد الولادات. تقدم عمر الحمل عند وجود دائ سكري مثبت وكذلك لدى الحوامل اللواتي لديهن مخاض باكر وانسمام حملي وسوابق إنتان بولي. أظهرت نتائج الزرع الجرثومي أن أشيع الجراثيم المسببة هي العصيات الكولونية بنسبة 51.4% . كما أظهرت نتائج التحسس الجرثومي للصادات أن أفضل الصادات تأثيرا على جميع الجراثيم هو الأميكاسين والسفترياكسون بنسبة 88.6% وأقلها تأثيرا الأمبيسلين 5.2% . We studied the pregnant women, who delivered in thr Gynecology and Obstetric department and clinic. In Al-Assad university hospital in lattakia. Whom suffer from different complains rather urological problems between 1L7L2003 and 1L6L2004. we found 35 cases (ASB) from 449 pregnant women in percentage 7.8% We had seen high percent of ASB coses in patients with increased age and increased number of birth. Increased age patients with previous his tory of urinary tract in fections or con firmed diabetes me llitus and prematine lobor. E-coli was the commonest Coues of Bocteriuriu 18 cases 51.4% The result of Antibiograms show that the best effecting antibiotics on all bacteria Ami Kacin and ceftriox one 88.6%.